Single-cell transcriptomics in thyroid eye disease - Sofia Ahsanuddin; Albert Y. Wu (Taiwan Journal of Ophthalmology)
Thyroid eye disease (TED) is a poorly understood autoimmune condition affecting the retroorbital tissue. Tissue inflammation, expansion, and fibrosis can potentially lead to debilitating sequelae such as vision loss, painful eye movement, proptosis, and eyelid retraction. Current treatment modalities for TED include systemic glucocorticoids, thioamides, methimazole, teprotumumab, beta-blockers, and radioactive iodine; however, it has been reported that up to 10%–20% of TED patients relapse after treatment withdrawal and 20%–30% are unresponsive to mainstay therapy for reasons that have yet to be more clearly elucidated. In the past 4 years, vision researchers have harnessed high-throughput single-cell RNA sequencing to elucidate the diversity of cell types and molecular mechanisms driving the pathogenesis of TED at single-cell resolution. Such studies have provided unprecedented insight regarding novel biomarkers and therapeutic targets in TED. This timely review summarizes recent breakthroughs and emerging opportunities for using single-cell and single-nuclei transcriptomic data to characterize this highly complex disease state. We also provide an overview of current challenges and future applications of this technology to potentially improve patient quality of life and facilitate reversal of disease endpoints.